5‐HT1 and 5‐HT2 Receptors Are Involved in the Anxiolytic‐Like Effects of the Neuronal NOS Inhibitor TRIM in the Rat. Issue 4 (6th March 2013) - Tanyeri, Pelin; Mutlu, Oguz; Ulak, Güner; Akar, Füruzan Yildiz; Celikyurt, Ipek Komsuoglu; Erden, Bekir Faruk
Abstract <table-wrap position="anchor" orientation="portrait"> <x xml:space="preserve">Table </x> Preclinical Research </table-wrap> TRIM, a selective neuronal NOS inhibitor, had anxiolytic effects in the elevated plus‐maze (EPM) test. The aim of the present study was to evaluate the involvement of serotonergic system in the anxiolytic‐like effect of TRIM in the EPM test, a widely used animal model of anxiety. The anxiolytic‐like effect of TRIM (50 mg/kg, i.p.) in adult Wistar albino male rats in the EPM test was antagonized by pretreatment with the 5‐HT depleting agent; parachlorophenylalanine methyl ester (3 × 150 mg/kg i.p.) that inhibits 5‐HT synthesis; methiothepin (0.1 mg/kg, i.p.), a nonselective 5‐HT receptor antagonist; WAY 100635 (0.1 mg/kg i.p.), a selective 5‐HT1A receptor antagonist; GR 127935 (3 mg/kg i.p.), a selective 5‐HT1B/1D receptor antagonist; cyproheptadine (3 mg/kg i.p.), a 5‐HT2 receptor antagonist; or ketanserin (5 mg/kg i.p.), a 5‐HT2A/2C receptor antagonist. The anxiolytic‐like effects of TRIM thus appear to be mediated in part by 5‐HT1 and 5‐HT2 receptors.